Laws of the State of Delaware 1816, An Act to Prevent the Discharging of Fire-Arms within the Towns and villages, and other public places within this State, and for Other Purposes. page 522 c. 192. - (:unkn) unknown (General Publisher, 1816)
if any person or persons shall presume to fire or discharge any gun, ordinance, musket, fowling-piece, fusee or pistol, within any of the towns or villages of this State, or within the limits thereof; or where the limits cannot be ascertained, within one quarter of a mile of the center of such town or village, shall fire or discharge any gun, ordinance, musket, fowling piece, fusee or pistol, within or on any of the greens, streets, alleys, or lanes of any of the towns and villages within this State, whereon any buildings are or shall be erected, or within one hundred yards of any mill-dam, over or across where any of the main public or State roads may go or pass; every person or persons so offending, shall be fined or punished as hereinafter directed.
--
Keywords: DISCHARGE